Vedolizumab clearance in neonates, susceptibility to infections and developmental milestones: a prospective multicentre population‐based cohort study. Issue 10 (2nd September 2021) - Julsgaard, Mette; Baumgart, Daniel C.; Baunwall, Simon M. D.; Hansen, Mette M.; Grosen, Anne; Bibby, Bo M.; Uldbjerg, Niels; Kjeldsen, Jens; Sørensen, Heidi G.; Larsen, Lone; Wildt, Signe; Weimers, Petra; et al.
Summary: Background: Little is known about the consequences of intrauterine exposure to, and the post‐natal clearance of, vedolizumab. Aims: To investigate the levels of vedolizumab in umbilical cord blood of newborns and rates of clearance after birth, as well as how these correlated with maternal drug levels, risk of infection and developmental milestones during the first year of life Methods: Vedolizumab‐treated pregnant women with inflammatory bowel disease were prospectively recruited from 12 hospitals in Denmark and Canada in 2016‐2020. Demographics were collected from medical records. Infant developmental milestones were evaluated by the Ages and Stages Questionnaire (ASQ‐3). Vedolizumab levels were measured at delivery and, in infants, every third month until clearance. Non‐linear regression analysis was applied to estimate clearance. Results: In 50 vedolizumab‐exposed pregnancies, we observed 43 (86%) live births, seven (14%) miscarriages, no congenital malformations and low risk of adverse pregnancy outcomes. Median infant:mother vedolizumab ratio at birth was 0.44 (95% confidence interval [CI], 0.32‐0.56). The mean time to vedolizumab clearance in infants was 3.8 months (95% CI, 3.1‐4.4). No infant had detectable levels of vedolizumab at 6 months of age. Developmental milestones at 12 months were normal or above average. Neither vedolizumab exposure in the third trimester (RR 0.54, 95% CI, 0.28‐1.03) nor combination therapy with thiopurines (RR 1.29, 95% CI, 0.60‐2.77) seemed to increase the risk of infections in the offspring. Conclusions: Neonatal vedolizumab clearance following intrauterine exposure is rapid. Infant vedolizumab levels did not correlate with the risk of infections during the first year of life. Continuation of vedolizumab throughout pregnancy is safe. Abstract : Vedolizumab clearance in neonates, susceptibility to infections and developmental milestones.